Electrochemical Behavior of Acid Orange 7 by Cyclic Voltammetry in Different Solvents - Ennouri,Rawdha (2017)
In the present work, the electrochemical oxidation of acid orange 7 (AO7) on a glassy carbon (GC) electrode has been investigated by cyclic voltammetry in different solvents: aqueous solvent (H2O), dimethyl sulfoxide (DMSO) and acetone (ACE), using sulfuric acid as a supporting electrolyte. The analysis of AO7 oxidation voltammograms in different solvents showed that the more donor numbers, the easier it becomes the oxidation of AO7. The experimental parameters show that the oxidation peak current of AO7 was linearly proportional to its concentration in a range from 0.04 mM to 0.2 mM. The limit of detection was estimated by gradually decreasing the concentration levels of AO7, and was found to be 6.6 μM.